Analysis of wardriving activity and WiFi access points - Eldaw, Elbaraa; Zeki, Akram M.; Senan, Shayma (Springer, 2013)
This paper proposes a system composed of hardware and software components that facilitates the activity of wardriving and assists in collecting statistical data by GPS of WiFi networks and their security status in particular area. The application has the potential of being used as a tool to study WiFi security trends or for misuse and WiFi exploitation.